Synthesis and biological evaluation of fluoropyrazolesulfonylurea and thiourea derivatives as possible antidiabetic agents. (1st November 2016) - Faidallah, Hassan M.; Al-Mohammadi, Manal M.; Alamry, Khalid A.; Khan, Khalid A.
Abstract: Fluorinated pyrazoles, benzenesulfonylurea and thiourea and their cyclic sulfonylthiourea derivatives were prepared as hypoglycemic agents. The chemistry involves the condensation of 4-hydrazino benzenesulfonamide hydrochloride with fluorochalcones to give pyrazoline derivatives which upon oxidation with bromine water afforded corresponding pyrazoles. Reaction of pyrazolines with isocyanates and isothiocyanates give the corresponding ureas and thioureas. Subsequent cyclization of these thiourea derivatives with ethyl bromoacetate and α-bromoacetophenone yielded the 4-oxothiazolidines and thiazolines, respectively. Preliminary biological screening of the prepared compounds revealed significant antidiabetic activity. Molecular and biological properties calculations revealed favorable drug-like profiles of six compounds. The structure–activity relationship (SAR) and in silico drug relevant properties calculations (HBD, HBA, tPSA, miLogP, molecular weight, % ABS, drug-likeness and drug score) endorse that these compounds are potential leads for future drug discovery study.